If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1(-4) = 8(x + 3) Multiply -1 * -4 y + 4 = 8(x + 3) Reorder the terms: 4 + y = 8(x + 3) Reorder the terms: 4 + y = 8(3 + x) 4 + y = (3 * 8 + x * 8) 4 + y = (24 + 8x) Solving 4 + y = 24 + 8x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = 24 + -4 + 8x Combine like terms: 4 + -4 = 0 0 + y = 24 + -4 + 8x y = 24 + -4 + 8x Combine like terms: 24 + -4 = 20 y = 20 + 8x Simplifying y = 20 + 8x
| -2(2y-4)-y=2(y-2) | | 5(x-10)=15x | | 7x+4x-8x=6 | | C^2-16c+64=0 | | 32-(1.5)(9.5)= | | 245x+54=40x-12 | | -1.4-3x=12.4 | | 4s=75+3s | | 6x-x=0 | | 6m-9m+m= | | 3x-17=5x+7 | | 1/2x+8=9 | | 5p-2+3p=-2 | | (-16+24x)=22 | | 15x^2+2t-1=0 | | 2x+16=7x-54 | | -2v+5v=6 | | n+2n=-18 | | (Y+4+3)=(y+2) | | 144=4+10x | | .50x+.8(40)=.25(92) | | 3x^2(9)=20 | | x^2+124x+49=1000 | | 3m+5m=-16 | | 2y=9x+2 | | -4n-n=-5 | | 9j-3k-4k+5k= | | k+6+6k=-15 | | 3x^2(16)=20 | | 8x-x^2=11 | | 4k*2-28k=-49 | | 1-5x-3=3 |